Incorporação do óleo essencial de Butia capitata como antibacteriano em um adesivo experimental - Peralta, Sonia Luque (2011)
The aim of this study was to evaluate the antimicrobial effect and physical mechanical properties of a self-etching experimental adhesive after the incorporation of an essential oil obtained from Butiá´s seeds (Butia capitata). It was formulated a two-step self-etching adhesive system composed of dentin primer and bond (cover resin). The primer was prepared with fixed amounts of 2-Hidroxiethyl methacrylate (HEMA), phosphoric acid ester monomer and solvent. The cover resin (bond) was prepared with a homogeneous mixture of Biphenyl-A glicidil dimethacrylate (Bis-GMA), Triethyleneglycol dimethacrylate (TEGDMA), HEMA, photoinitiators as camphoroquinone (CQ) and Ethyl 4-dimethyl amine benzoate (EDMAB); and 1% Butia Capitata‟ seeds oil (butiá). Three adhesives have been tested as commercial references: Clearfil Protect Bond (CPB), Clearfil SE Bond (CSEB) and Adper SE Plus (AP), and two experimental adhesives: Control adhesive without oil (CA), and experimental adhesive containing butiá´s oil (EA). The antimicrobial effect of adhesives was evaluated by the methods of biofilm growth inhibition in a Streptococcus mutans monoculture assay and by the microcosm technique. The physical mechanical performance of these adhesives was evaluated by micro tensile bond strength (μTBS), degree of conversion (DC), and water sorption (WS) and solubility (SL). It also was evaluated the biocompatibility by the genotoxicity and cytotoxicity assays. The data were statistically analyzed by analysis of variance and complementary tests. In the assay of anti-S. mutans biofilm , AP showed the highest effect, followed by EA and CPB. In the microcosm assay, high viability was found in AC for total microorganisms, and minor viability was found in C, EA and CPB for total aciduric. While for total Lactobacillus most viability was found in C and AC, and for S. mutans , all groups had similar values. For the GC, WA, SL e μTBS tests EA was similar to CA, but after six months of aging the μTBS values were reduced for EA. Regarding the cytotoxicity the CPB primer and the AP bond were the most toxic, and regarding genotoxicity all groups have had similar results. According to results obtained, we can conclude that EA have similar immediate antimicrobial effect, physical-mechanical properties and toxicity to commercial adhesives, but after six months the microtensile strength was reduced, but similar to commercial references